Randomized study evaluating the efficacy and safety of switching from an an abacavir/lamivudine-based regimen to an elvitegravir/cobicistat/emtricitabine/tenofovir alafenamide single-tablet regimen. (1st August 2019) - Rizzardini, Giuliano; Gori, Andrea; Miralles, Celia; Olalla, Julián; Molina, Jean-Michel; Raffi, François; Kumar, Princy; Antinori, Andrea; Ramgopal, Moti; Stellbrink, Hans-Jürgen; Das, Moupali; Chu, Hoa; et al.
Abstract : Objective: To evaluate the efficacy and safety of switching from an abacavir/lamivudine (ABC/3TC)-based regimen to an elvitegravir/cobicistat/emtricitabine/tenofovir alafenamide (E/C/F/TAF) single-tablet regimen in virologically suppressed, HIV-1-infected adults. Design: Randomized, open-label, noninferiority study. Methods: Participants with HIV-1 RNA levels less than 50 copies/ml receiving ABC/3TC plus a third agent for at least 6 months were randomized 2 : 1 to switch immediately to E/C/F/TAF (immediate-switch group) for 48 weeks or to continue receiving ABC/3TC plus a third agent for 24 weeks followed by E/C/F/TAF for 24 weeks (delayed-switch group). The primary endpoint was HIV-1 RNA less than 50 copies/ml at Week 24 by Food and Drug Administration Snapshot algorithm (−12% noninferiority margin). Results: Baseline characteristics of 274 participants (183 in immediate-switch group and 91 in delayed-switch group) were similar. Virologic response was maintained at Week 24 by 93.4 and 97.8% of participants in the immediate-switch and delayed-switch groups, respectively, with a treatment difference of −4.4% (95% confidence interval: −9.4 to 1.9%), confirming noninferiority. Adverse events of any grade were similar between groups through Week 24 (66% E/C/F/TAF, 64% ABC/3TC); adverse event-related drug discontinuations occurred in 4% of participants switching to E/C/F/TAF (no discontinuations because of renal events) and no participants continuing ABC/3TC. Renal biomarkers of urine albumin:creatinine and beta-2-microglobulin:creatinine ratios significantly improved on E/C/F/TAF. Self-reported treatment satisfaction was significantly higher with E/C/F/TAF. Conclusion: Switching to E/C/F/TAF was noninferior to continuing ABC/3TC plus a third agent for maintenance of HIV RNA suppression at Week 24. This study supports E/C/F/TAF as an efficacious and well tolerated option for participants switching from ABC/3TC-based regimens. Abstract : Supplemental Digital Content is available in the text